ANALISIS FAKTOR PENYEBAB PENYAKIT TBC DI JAWA BARAT MENGGUNAKAN REGRESI BINOMIAL NEGATIF - Zeanova, Humaira; Taniwan, Peter; Aulia Putri, Rahma; Yusti Faidah, Defi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The realization of "Indonesia Emas 2045" is significantly determined by the current Golden Generation. It is expected that this generation possesses high competence, quality, and innovation. As the most populous province in Indonesia, West Java plays a crucial role in achieving the vision of "Indonesia Emas 2045," particularly in the Human Development pillar through the enhancement of health standards. However, infectious diseases have become a major barrier to realizing this vision, with tuberculosis (TB) being one of the most prevalent. In 2023, there were 204,934 reported TB cases in West Java. Therefore, this study aims to identify the factors influencing the number of TB cases in West Java. The data type for TB cases is count data, thus the approach used in this study is Poisson regression, with Negative Binomial regression as an alternative to address overdispersion. The results indicate that the number of community health centers (X1), the percentage of standard-compliant drinking water facilities (X2), and the Air Quality Index (X4) have a significant impact on the number of TB cases in West Java. This is demonstrated by the p-value of each variable, where variables X1, X2, and X4 all have a p-value of 0.0, except for the percentage of households with adequate sanitation (X3), which has a p-value of 0.063 in the Negative Binomial regression. Based on these factors, it is hoped that the government can optimize related programs and facilities to reduce the number of TB cases in West Java and contribute to realizing one of the pillars of "Indonesia Emas 2045."